HUBUNGAN TINGKAT PENGETAHUAN KREDENSIALING KEPERAWATAN DENGAN MOTIVASI MENYELENGGARAKAN PRAKTIK MANDIRI MAHASISWA PROGRAM D III KEPERAWATAN DI SURAKARTA - Diyono Diyono; Shara Audia Nanda S. (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2016)
AbstractKredensialing nursing encourages nurses apparently not motivated through independentpractice. The number of nurses who carry out independent practice very few comparedwith the number of nurses in Indonesia. to know (1) the level of student knowledge aboutnursing kredentialing (2) The level of student motivation conducting independent practice(3) the relationship with the level knowledge of nursing kredentialing with motivationorganize independent practice Student Nursing Program Diploma III in Surakarta.Design of this research is correlational, with subjects study is 153 students of Diploma IIIof Nursing (76 from Surakarta Health Polytechnic and 77 from Panti Kosala NursingAcademy).Results of this research are (1) Average knowledge level of nursing kredentialing ismoderate,value of 15.89 (2) The level of motivation conducting independent practicenursing is 43.03, moderate (3) There is a positive relationship between the level ofknowledge about nursing kredensialing by organizing motivational practices independentin students Program D III of nursing in Surakarta 2016. The conclussion is a positiverelationship, with a low level of correlation between the knowledge of credentialingnursing with motivation organize independent practice in students of Nursing ProgramDiploma III in Surakarta (p: 0.039;r:0.167)Keywords: Nursing Kredentialing, Independent Nursing Practice